2022
DOI: 10.1136/ejhpharm-2022-003544
|View full text |Cite
|
Sign up to set email alerts
|

Management of nirmatrelvir/ritonavir and tacrolimus interaction in kidney transplant recipients infected by COVID-19: a three-case series

Abstract: Objectives Nirmatrelvir/ritonavir may cause a clinically relevant drug-drug interaction (DDI) with immunosuppressive drugs, such as tacrolimus, which may condition the use of this antiviral in transplant patients. We aimed to describe the management of this interaction. Methods Descriptive study in which renal transplant patients in treatment with nirmatrelvir/ritonavir and tacrolimus were included. They suspended tacrolimus the day before starting the antiviral treatment, and the decision to restart it was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…There are six previous reports in 44 patients of strategies to mitigate this drug-drug interaction between NIM/r and tacrolimus limited only to solid organ transplant recipients, as summarized in Table 1 [16‒21]. Like the observations in the results from the strategies herein, they all support discontinuation of tacrolimus during NIM/r and the need for close, up to daily, monitoring of tacrolimus concentrations.…”
Section: Discussionsupporting
confidence: 61%
“…There are six previous reports in 44 patients of strategies to mitigate this drug-drug interaction between NIM/r and tacrolimus limited only to solid organ transplant recipients, as summarized in Table 1 [16‒21]. Like the observations in the results from the strategies herein, they all support discontinuation of tacrolimus during NIM/r and the need for close, up to daily, monitoring of tacrolimus concentrations.…”
Section: Discussionsupporting
confidence: 61%
“…We reviewed the literature on organ transplant patients using TAC-ER in combination with NMV/r. Table 1 presents the background of post-solid organ transplant patients using TAC-ER in combination with NMV/r and Table 2 presents the blood TAC level course of these patients [ 20 - 23 ]. All patients using TAC-ER, except for the present patient, were post-kidney transplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recent study conducted by Guzmán Cordero and Saez-Torres de Vicente,1 which reported how to manage patients treated with nirmatrelvir/ritonavir (brand name Paxlovid) and tacrolimus. The results hinted that nirmatrelvir/ritonavir combined with tacrolimus interaction could be controlled and achieve a good clinical effect.…”
mentioning
confidence: 99%
“…Tacrolimus is mandatory in patients with chronic renal failure in the department of nephrology, especially in those who do not respond well to hormone use. Guzmán Cordero and Saez-Torres de Vicente1 published papers with profound guidance for us to manage chronic renal failure well with tacrolimus during the COVID-19 pandemic background.…”
mentioning
confidence: 99%